2018
DOI: 10.1002/chem.201802287
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric XNA: An Unconventional Design for Orthogonal Informational Systems

Abstract: The paradigm of homogenous-sugar-backbone of RNA and DNA has reliably guided the construction of many functional and useful xeno nucleic acid (XNA) systems to date. Deviations from this monotonous and canonical design, in many cases, results in oligonucleotide systems that lack base pairing with themselves, or with RNA or DNA. Here we show that nucleotides of two such compromised XNA systems can be combined with RNA and DNA in specific patterns to produce chimeric-backbone oligonucleotides, which in certain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…For example, nucleic acid polymers with non-inheritable backbone heterogeneities (e.g. 2 0 -5 0 versus 3 0 -5 0 backbone heterogeneity for RNA [54] or mixed nucleotide backbones formed from RNA, DNA or other nucleic acid types [55]) have fascinating properties. In particular, some chimeric backbones decrease duplex stabilities, which could help to mitigate the strand dissociation problem [56].…”
mentioning
confidence: 99%
“…For example, nucleic acid polymers with non-inheritable backbone heterogeneities (e.g. 2 0 -5 0 versus 3 0 -5 0 backbone heterogeneity for RNA [54] or mixed nucleotide backbones formed from RNA, DNA or other nucleic acid types [55]) have fascinating properties. In particular, some chimeric backbones decrease duplex stabilities, which could help to mitigate the strand dissociation problem [56].…”
mentioning
confidence: 99%
“…An interesting development in this context is the discovery that mixed backbone chemistries can display novel emergent properties. For example, Krishnamurthy and colleagues probed the ability of XNA-RNA chimeric oligonucleotides to hybridize with their natural nucleic acid counterparts and found that the otherwise non-pairing ribuloNA can be interspersed with RNA or DNA building blocks to yield oligonucleotides with comparable or higher duplex thermal stability than natural systems and tuneable base-pairing properties [ 26 ]. The authors suggest that such a system could be used to mimic natural base-pairing rules with a reduced number of bases, storing information in the sugar in place of the GC base pair.…”
Section: Expanding the Chemistry Of Nucleic Acidsmentioning
confidence: 99%
“… 19 , 21 , 25 and 48 ) offer a means to navigate a greater variety of chemical and structural space, potentially enabling discovery and evolution of more diverse functional 3D motifs and properties made possible by interactions between alternative polymer chemistries. 49 Here, we expand the range of mixed-chemistry synthetic genetic systems using two XNA polymerase blends to efficiently synthesise and reverse transcribe mixtures of LNA and/or 2′OMe-RNA.…”
Section: Introductionmentioning
confidence: 99%